2-Bromopalmitate attenuates inflammatory pain by maintaining mitochondrial fission/fusion balance and function. (30th November 2020) - Xie, Min; Cheng, Menglin; Wang, Bojun; Jiao, Ming; Yu, Liangzhu; Zhu, Haili
Abstract: Inflammatory pain activates astrocytes and increases inflammatory cytokine release in the spinal cord. Mitochondrial fusion and fission rely on the functions of dynamin-related protein 1 (Drp1) and optic atrophy 1 (OPA1), which are essential for the synaptic transmission and plasticity. In the present study, we aimed to explore the effects of 2-bromopalmitate (2-BP), an inhibitor of protein palmitoylation, on the modulation of pain behavior. Rats were intraplantar injected with complete Freund's adjuvant (CFA) to establish an inflammatory pain model. In the spinal cord of rats with CFA-induced inflammatory pain, the expression of astrocyte-specific glial fibrillary acidic protein (GFAP) and contents of proinflammatory cytokines IL-1β and TNF-α were increased. Mitochondrial Drp1 was increased, while OPA1 was decreased. Consequently, CFA induced reactive oxygen species (ROS) production and Bcl-2-associated X protein (BAX) expression. The intrathecal administration of 2-BP significantly reversed the pain behaviors of the inflammatory pain in rats. Moreover, 2-BP also reduced the Drp1 expression, elevated the OPA1 expression, and further reduced the GFAP, IL-1β, and TNF-α expression and ROS production. Furthermore, in vitro study proved a similar effect of 2-BP on the regulation of Drp1 and OPA1 expression. 2-BP also increased the mitochondrial membrane potential and decreased the levels of BAX, ROS, and proinflammatory cytokines. These results indicate that 2-BP may attenuate the inflammatory pain of CFA-treated rats via regulating mitochondrial fission/fusion balance and function.